2010
DOI: 10.1590/s0102-76382010000200011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of traditional long incision vein harvesting and multiple incisions with small skin bridges in patients with coronary artery bypass grafting at King Abdullah University Hospital - Jordan

Abstract: Estudo comparativo entre a exérese da veia safena tradicional por incisão contínua e incisões múltiplas com pequenos "patchs" de pele em pacientes submetidos à revascularização do miocárdio no Hospital Universitário King Abdullah -Jordânia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Saphenous harvesting was studied by Hijazi10, who compared the difference in wound complication and infection rates between two saphenous vein harvesting techniques, long incision versus multiple short interrupted incisions (tunneling) for coronary artery bypass grafting at King Abdullah University Hospital – Jordan and found that veins harvested using saphenous vein tunneling were associated with fewer wound complications than the traditional longitudinal method.…”
Section: Introductionmentioning
confidence: 99%
“…Saphenous harvesting was studied by Hijazi10, who compared the difference in wound complication and infection rates between two saphenous vein harvesting techniques, long incision versus multiple short interrupted incisions (tunneling) for coronary artery bypass grafting at King Abdullah University Hospital – Jordan and found that veins harvested using saphenous vein tunneling were associated with fewer wound complications than the traditional longitudinal method.…”
Section: Introductionmentioning
confidence: 99%
“…Wound complication rates with this approach are 3.2% to 25%. [10][11][12][13][14] Endoscopic vein harvest (EVH) is widely used in coronary artery bypass grafting due to a perceived reduction in wound-related complications, improved patient satisfaction, lower postoperative pain, and reduced postoperative length of stay. Nonetheless, EVH has been used less frequently in lower extremity bypass.…”
mentioning
confidence: 99%
“…The length of the incision made depends on how much venous conduit is required to perform the coronary bypasses . A bridging technique, which involves making several smaller “skip incisions,” was identified as an effective solution in reducing wound complications in comparison with the long incision approach . The conventional saphenectomy approach involves the longitudinal opening of the fascial canal surrounding the vein, formed predominantly by adipose tissue .…”
Section: Conventional Open Vein Harvesting Techniquementioning
confidence: 99%
“…Plaques in SVGs are known to be diffuse, poorly calcified, and characterized by fibroadenomas with large necrotic cores rich in inflammatory and foam cells . The thin fibro‐lipidic layer encapsulating the formed plaque is highly susceptible to rupture, paving the way for graft failure via thrombosis …”
Section: Introductionmentioning
confidence: 99%